Echo and Drag as Resistance: Coloniality, Queerness, and Practices of Reading Student Texts - Joshua Barsczewski; Florianne Jimenez (Journal of the Assembly for Expanded Perspectives on Learning, 2024)
In this article, a postcolonial theorist and a queer studies scholar reconsider the role of student resistance in Writing Studies’ social justice turn, arguing for a way of reading student texts that accounts for why students might choose to take up social justice or not in their own writing. Through examples from their ongoing research projects, the writers discuss how students’ resistance surfaced not as visible and explicit signs of a changed epistemological framework or political perspective, but as a series of normative rhetorical choices that made space for more transgressive or subversive possibilities.